Is Interictal EEG Correlated with the Seizure Type in Idiopathic (Genetic) Generalized Epilepsies? - ASADI-POOYA, Ali Akbar; EMAMI, Mehrdad (Iranian Journal of Child Neurology, 2012)
How to Cite this Article: Asadi-pooya AA, Emami M. Is Interictal EEG Correlated with the Seizure Type in Idiopathic (Genetic) Generalized Epilepsies? Iran J Child Neurol 2012;6(2): 25-28. Objective We investigated the correlation between different interictal EEG abnormalities observed in patients with idiopathic (genetic) generalized epilepsies (IGEs) and their seizure types. Material & Methods In this cross-sectional study, all patients with the diagnosis of IGE, were recruited in the outpatient epilepsy clinic at Shiraz University of Medical Sciences, Iran, from 2008 through 2010. Demographic variables and relevant clinical and EEG variables were summarized descriptively. Statistical analyses were performed using independent samples T-test, Chi square and Fisher’s Exact tests to determine potentially significant differences. Results Three-hundred thirty-six patients were diagnosed ashaving IGE. Interictal EEG findings in patients with generalized tonic-clonic seizure (GTCS) compared to patients without GTCS were not different. Abnormal EEG findings in patients with myoclonic seizures compared to patients without these were not different either. However, normal EEGs were more frequently observed in patients with history of myoclonic seizures (P = 0.0001). EEG findings in patients with absences compared to patients without absences were not different. Conclusion Interictal EEG cannot differentiate the seizure types and therefore different syndromes of IGEs. Polyspikes, 3-Hz generalized spike-wave (GSW) complexes and 3.5 - 6 Hz GSW complexes, alone or in combinations, could be observed in various seizure types and syndromes of IGE. The key element in making the correct diagnosis is a detailed clinical history. References Panayiotopoulos CP. Idiopathic generalized epilepsies. In: Panayiotopoulos CP, editor. The epilepsies: seizures, syndromes and management. Oxford: Bladon Medical Publishing 2005. p. 271-348. Lagerlund TD, Cascino GD, Cicora KM, Sharbrough FW. Long-term electroencephalographic monitoring for diagnosis and management of seizures. Mayo Clin Proc 1996 Oct;71(10):1000-6. Betting LE, Mory SB, Lopes-Cendes I, Li LM, Guerreiro MM, Guerreiro CA et al. EEG features in idiopathic generalized epilepsy: clues to diagnosis. Epilepsia 2006 Mar;47(3):523-8. Yenjun S, Harvey AS, Marini C, Newton MR, King MA, Berkovic SF. EEG in adult-onset idiopathic generalized epilepsy. Epilepsia 2003 Feb;44(2):252-6. Blume WT, Lüders HO, Mizrahi E, Tassinari C, van Emde Boas W, Engel J Jr. Glossary of descriptive terminology for ictal semiology: report of the ILAE task force on classification and terminology. Epilepsia 2001;42(9):1212-8. Engel J Jr. A proposed diagnostic scheme for people with epileptic seizures and epilepsy: report of the ILAE task force on classification and terminology. Epilepsia 2001 Jun;42(6):796-803. Engel J. Jr. Report of the ILAE Classification Core Group. Epilepsia 2006 Sep;47(9):1558-68. Asadi-Pooya AA, Emami M. Effects of antiepileptic drugs on electroencephalographic findings in patients with idiopathic generalized epilepsies. Iran J Child Neurol 2011;5(4):33-6. Asadi-Pooya AA, Emami M, Nikseresht A. Early-onset versus typical childhood absence epilepsy; clinical and electrographic characteristics. Seizure 2012;21:273-5. Nordi DR. Idiopathic generalized epilepsies recognized by the International League Against Epilepsy. Epilepsia 2005;46(Suppl. 9):48-56. Panayiotopoulos CP. Syndromes of idiopathic generalized epilepsies not recognized by the International League Against Epilepsy. Epilepsia 2005;46(Suppl. 9):57-66. Asadi-Pooya AA, Sperling MR. Choices of antiepileptic drugs based on specific epilepsy syndromes and seizure types. In: Asadi-Pooya AA, Sperling MR. Antiepileptic Drugs: A Clinician’s Manual. Oxford, UK: Oxford University Press; 2009. p. 95-102.